Analysis of Agricultural Input Resources on Chopped Tobacco Production of Reket and Seram Varieties in Suralaga District East Lombok Regency - Dudi Septiadi; Muhammad Nursan; Aeko Fria Utama FR; Pande Komang Suparyana; Baiq Saopi Nadiawati (Jurnal Biologi Tropis, 2022)
Tobacco is a leading commodity that has high economic value. The tobacco products industry has a major contribution to the structure of state revenues through excise taxes, employment and sources of farmers' income. This research aims to; 1) explain the relevance of the characteristics of farmers and the production of chopped tobacco in Suralaga sub-district, East Lombok Regency; 2) analyze the influence of farming input resources on the production of reket and seram tobacco varieties in Suralaga District, East Lombok Regency. The research was conducted in Suralaga District, East Lombok Regency. The study was conducted from July 2021 - November 2021. The sampling method used purposive sampling as many as 40 farmer respondents who run tobacco farming. The data analysis method used in this research is quantitative analysis with multiple linear regression approaches. The results of the research show that the agricultural input resource variables that affect the production of tobacco farming are tobacco farming land variables, pesticides, labour, farming experience, and age. While the dummy variables in this study, namely the gender and variety types were also stated as variables that had an effect on tobacco production.